Injectable Prevascularized Mature Adipose Tissues (iPAT) to Achieve Long‐Term Survival in Soft Tissue Regeneration. Issue 23 (28th September 2022) - Louis, Fiona; Sowa, Yoshihiro; Irie, Shinji; Higuchi, Yuriko; Kitano, Shiro; Mazda, Osam; Matsusaki, Michiya
Abstract: Soft tissue regeneration remains a challenge in reconstructive surgery. So far, both autologous fat implantations and artificial implants methods used in clinical applications lead to various disadvantages and limited lifespan. To overcome these limitations and improve the graft volume maintenance, reproducing a mature adipose tissue already including vasculature structure before implantation can be the solution. Therefore, injectable prevascularized adipose tissues (iPAT) are made from physiological collagen microfibers mixed with human mature adipocytes, adipose‐derived stem cells, and human umbilical vein endothelial cells, embedded in fibrin gel. Following murine subcutaneous implantation, the iPAT show a higher cell survival (84% ± 6% viability) and volume maintenance after 3 months (up to twice heavier) when compared to non‐prevascularized balls and liposuctioned fat implanted controls. This higher survival can be explained by the greater amount of blood vessels found (up to 1.6‐fold increase), with balanced host anastomosis (51% ± 1% of human/mouse lumens), also involving infiltration by the lymphatic and neural vasculature networks. Furthermore, with the cryopreservation possibility enabling their later reinjection, the iPAT technology has the merit to allow noninvasive soft tissue regeneration for long‐term outcomes. Abstract : By mixing mature fat cells (adipocytes), adipose stem cells, and vascular cells it is possible to create injectable and cryopreservable prevascularized mature adipose tissue balls. These balls then merge together after injection to make a bigger size tissue, which shows a high long‐term survival for soft tissue regeneration, compared with general surgery using classic fat injection.